(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
Solvent partitioning followed by column chromatography of the MeOH extract of the seeds of Swietenia mahagoni afforded two limonoids, swietenolide (compound 1) and 2-hydroxy-3-O-tigloylswietenolide (compound 2), later one is new compound. The compounds were identified by spectroscopic means. The cytotoxic activity of these compounds was assessed by using the conventional brine shrimp lethality bioassay. While both compounds were found to have moderate cytotoxic activity, compound 2 displayed overall more potent activity than compound 1. Key words: Cytotoxic; Limonoid; Swietenia mahagoni; Brine shrimp lethality bioassay DOI: 10.3329/bjpp.v24i1.5729 Bangladesh J Physiol Pharmacol 2008; 24(1&2) : 1-6